"A link to the outside:" Patient perspectives on a mobile texting program to improve depression self-management. Issue 9 (September 2021) - Van Tiem, Jen; Moeckli, Jane; Suiter, Natalie; Fuhrmeister, Lindsey; Pham, Kassi; Dindo, Lilian; Turvey, Carolyn
Highlights: Daily text messages prompted patients to reflect upon their mood. Patients valued reviewing graphs of their mood over time. Patients shared their graphs and texts with providers and family members. Abstract: Background: The effectiveness of technology-assisted interventions designed to ameliorate depressive symptoms and improve antidepressant medication adherence is hampered by diminished usage over time and poor integration with clinical care. Objective: This manuscript presents patient perspectives on a texting and secure messaging intervention designed to engage providers and patients during a targeted transition period when patients were initiating a new antidepressant medication. Patient involvement: Development of the intervention was guided by feedback from a presentation and discussion with an engagement panel of local stakeholders, including patients, who meet quarterly with research investigators. Methods: Semi-structured, qualitative, telephone interviews were conducted with 21 participants. Interviews were designed to identify the themes of self-determination and planned behavior in using the text messaging intervention. Qualitative analysis of participants' experiences used inductive and deductive coding, as well as pile sorting. Results: The intervention prompted participants to reflect about how they manage their mood, engage in behaviors guided by their values, and commit to making positive changes in how they acted in real-time. Elements of the intervention facilitated participant conversations with trusted friends and family over time about what had influenced their actions and feelings. Discussion: The texting intervention appeared to help participants live a life consistent with their values. However, we were unable to recruit mental health providers to participate. Practical value: Technology to promote self-reflection and an "observing self" may work best when done in dialogue with important others, including mental health providers. Future directions of this research should find ways to understand provider buy-in, or lack thereof, in e-health interventions.